1993
DOI: 10.1002/mrd.1080350106
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear transfer in cattle: Effect of nuclear donor cells, cytoplast age, co‐culture, and embryo transfer

Abstract: There are many factors affecting the efficiency of nuclear transfer technology. Some are evaluated here using our novel approach by enucleating oocytes at 20-22 hr after in vitro maturation (IVM), culturing the enucleated oocytes (cytoplasts) for 8-10 hr or 18-20 hr to gain activation competence and then conducting nuclear transfer. In the first experiment, we demonstrated that cumulus cell (CC) monolayer can support some cloned embryos to develop into morulae or blastocysts. Co-culture with CC and bovine ovid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 30 publications
5
33
0
Order By: Relevance
“…Our study supports the observation that activation of recipient cytoplasts prior to nuclear transfer improves development of cloned embryos (Barnes et al, 1993;Campbell et al, 1994;Kono et al, 1994;Stice et al, 1994). It is known that the co-culture system was effective in promoting development of bovine embryos in vitro (Eyestone and First, 1989;Hernandez-Ledezma et al, 1993) including cloned embryos (Barnes et al, 1993;Van Stekelenburg-Hamers et al, 1993;Yang et al, 1993a;Kono et al, 1994).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Our study supports the observation that activation of recipient cytoplasts prior to nuclear transfer improves development of cloned embryos (Barnes et al, 1993;Campbell et al, 1994;Kono et al, 1994;Stice et al, 1994). It is known that the co-culture system was effective in promoting development of bovine embryos in vitro (Eyestone and First, 1989;Hernandez-Ledezma et al, 1993) including cloned embryos (Barnes et al, 1993;Van Stekelenburg-Hamers et al, 1993;Yang et al, 1993a;Kono et al, 1994).…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, electrical activation of the in vitro matured bovine oocytes was found to be oocyteage-dependent and poor activation results were obtained with oocytes matured in vitro less than 30 h (Ware et al, 1989;Yang et al, 1991 Thus, at one time, most nuclear transfer programs involved using aged oocytes as recipients (Willadsen et al, 1991;Westhusin et al, 1992;Yang et al, 1993a). More recently, improvements on activation procedures have resulted in suc-cessful activation and led to the use of young oocytes for nuclear transfer (First et al, 1992;Barnes et al, 1993;Yang et al, 1993b;Aoyagi ef al, 1994;Heyman et al, 1994;Stice et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Developmental rates to the blastocyst stage similar to those reported using in vivo procedures have been obtained in vitro (3), suggesting that temporary passage in the reproductive tract of nuclear transfer embryos is not necessary. In vitro derived donor embryos have previously been shown to support the development of single generation nuclear transfer embryos with a potential to produce live offspring (3,5,10). Although some authors have reported reduced development from in vitro donor embryos (10), others have shown similar development rates of nuclear transfer embryos derived from in vitro and in vivo donor embryos (2,3).…”
Section: Discussionmentioning
confidence: 99%